2017
DOI: 10.4291/wjgp.v8.i3.133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of replenishment of vitamin D on survival in patients with decompensated liver cirrhosis: A prospective study

Abstract: AIMTo assess the vitamin D (VD) deficiency as a prognostic factor and effect of replenishment of VD on mortality in decompensated cirrhosis.METHODSPatients with decompensated liver cirrhosis were screened for serum VD levels. A total of 101 VD deficient patients (< 20 ng/mL) were randomly enrolled in two groups: Treatment group (n = 51) and control group (n = 50). Treatment group received VD treatment in the form of intramuscular cholecalciferol 300000 IU as loading dose and 800 IU/d oral as maintenance dose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Findings are also conflicting with regard to the effect of vitamin D supplementation in the case of advanced liver disease. In a cohort of advanced decompensated cirrhotic patients (Child-Pugh C, score of ≥ 10) randomly assigned to vitamin D treatment or a control receiving standard care and followed for 6 mo, the survival, as well as Child-Pugh and MELD scores, were comparable between the groups[ 48 ]. Nevertheless, supplementation of high-dose oral vitamin D resulted in several clinical improvements such as an anti-depressant effect among patients with chronic liver disease (mainly women)[ 78 ], and 60% risk reduction for acute rejection among patients after LT[ 79 ].…”
Section: Micronutrient Status and Recommended Supplementation In Patimentioning
confidence: 99%
“…Findings are also conflicting with regard to the effect of vitamin D supplementation in the case of advanced liver disease. In a cohort of advanced decompensated cirrhotic patients (Child-Pugh C, score of ≥ 10) randomly assigned to vitamin D treatment or a control receiving standard care and followed for 6 mo, the survival, as well as Child-Pugh and MELD scores, were comparable between the groups[ 48 ]. Nevertheless, supplementation of high-dose oral vitamin D resulted in several clinical improvements such as an anti-depressant effect among patients with chronic liver disease (mainly women)[ 78 ], and 60% risk reduction for acute rejection among patients after LT[ 79 ].…”
Section: Micronutrient Status and Recommended Supplementation In Patimentioning
confidence: 99%
“…For example, zinc supplementation was noted to reduce the impact of HE (specifically owed to its facilitation of the urea cycle) and the incidence of hepatocellular carcinoma (31). Vitamin D supplementation can help to increase the survival odds of cirrhotic patients and augment the immune response in cases of spontaneous bacterial peritonitis (60). Magnesium repletion has been demonstrated to slow disease progression, exert hepatoprotective qualities, and even limit hepatitis C virus (HCV) replication (15).…”
Section: Obtain Baseline Laboratories/electrolyte and Vitamin Repletionmentioning
confidence: 99%
“…In fact, there was a higher incidence of overt HE in patients with low levels of 25‐OHD at similar levels of disease severity . It has been shown that vitamin D replenishment may improve survival in patients with decompensated liver cirrhosis possibly by improving the defense against viral and bacterial pathogens . Thus, vitamin D supplementation has been suggested in cirrhotic patients with serum levels of 25(OH) vitamin D < 30 ng/mL, through administration of 5000 IU/d vitamin D 3 or 50,000 IU/wk vitamin D 2 or D 3 for 3 months followed by indefinite administration of 1000 IU/d .…”
Section: Sodium Zinc Thiamin and Vitamin D In Hepatic Encephalopathymentioning
confidence: 99%